RENEWAL OF ISLAMIC LAW IN INDONESIA: A STUDY OF YUDIAN WAHYUDI'S THOUGHT - Wardah Nuroniyah (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The purpose of this study is to describe the results of Yudian Wahyudi's thoughts on the renewal of Islamic law in Indonesia. This type of research is library research using a qualitative descriptive approach to describe the current phenomenon. This analysis seeks to see the socio-cultural background, the context of the readers and the text of books and articles about Yudian Wahyudi's thoughts related to the problems to be studied. The results of this study explain that Islamic law reform underwent a radical transformation with the emergence of several calls about Indonesian fiqh and Indonesian schools of thought by scholars such as Ash Shiddieqy and Hazairin who criticized puritans who often echoed Arabization of fiqh, both promoting the richness of Indonesian culture and traditions as a valid source. for the implementation of the law by trying to modernize the application of Islamic law with the help of modern knowledge and science. Yudian Wahyudi's thinking in the renewal of Islamic law offers an applicative methodological approach through the concept of returning to the Qur'an and Hadith, the concept of fiqh and maqashid sharia by trying to dialogue between sharia texts, and empirical 'urf, both of which complement each other. Different from the previous figure, the Islamic renewal proposed by Yudian Wahyudi is not only a theoretical offer but can also be implemented practically.